Optimasi Rute Pengawasan Pendistribusian Logistik (Perlengkapan Pemungutan Suara : Surat Suara, Kotak Suara, Bilik Pemungutan Suara, Segel, dan Tinta) di Wilayah Kabupaten Simalungun Pada Tahapan Pemilu Tahun 2029 Menggunakan Metode Shortest Route Berbasi - Alfonso Pareandos Sitorus; Parapat Gultom (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Election logistics distribution is one of the most critical stages in the electoral process because it directly affects timeliness, security, and completeness of voting equipment delivery. Simalungun Regency consists of 32 districts with diverse geographical conditions, requiring efficient route planning for logistics supervision. This study aims to determine the optimal supervision route for election logistics distribution in the 2029 General Election using the Shortest Route method implemented in QM for Windows. A quantitative approach employing Network Analysis was adopted. The data include warehouse location, district election committee locations, road network, travel distance, and travel time. The analysis was performed using the Network module in QM for Windows to obtain the minimum-distance route. The findings indicate that grouping distribution routes into three operational regions improves travel efficiency and supports effective logistics supervision.